2014
DOI: 10.1111/1751-2980.12180
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, clinical features and management of acute recurrent pancreatitis

Abstract: The etiological factors of ARP are similar to those of acute pancreatitis at the first attack. The management of ARP should be fully considered based on etiological investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Patients with recurrent acute pancreatitis do not have continuous pain requiring treatment, clinical evidence of endocrine or exocrine pancreatic insufficiency, or permanent histologic changes such as calcification or fibrosis [25]. Studies suggest that 10–30% of patients with acute pancreatitis develop recurrent acute pancreatitis [1, 2628].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrent acute pancreatitis do not have continuous pain requiring treatment, clinical evidence of endocrine or exocrine pancreatic insufficiency, or permanent histologic changes such as calcification or fibrosis [25]. Studies suggest that 10–30% of patients with acute pancreatitis develop recurrent acute pancreatitis [1, 2628].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Clinical studies assessing the impact of HTG on the severity of AP have also shown conflicting results. [ 15 16 17 18 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently HTG is accepted as a major cause of RAP particularly in China. Deng et al reported that HTG accounted for 21% of RAP and biliary factor was still the leading causes of RAP in a region of China [19]. A multicenter study showed the recurrence rate of HTG-AP was obviously higher than other causes (15.29%, 7.73% and 9.75% for HTG-AP, biliary AP and alcoholic AP respectively) [6].…”
Section: Discussionmentioning
confidence: 99%